Intraoperative computer-assisted neuronavigation in functional neurosurgery - Tronnier, Volker; Wirtz, Christian Rainer; Knauth, Michael; Bonsanto, Matteo Mario; Haßfeld, Stefan; Albert, Friedrich; Kunze, Stefan (Stereotactic and functional neurosurgery, 1996)
The clinical experience with a frameless computer-assisted neuronavigational system (ISG, Canada) used in functional neurosurgery is described. The advantage of image-guided surgery is stressed for functional procedures of the cortex with delineation of the gyral pattern, e.g. motor cortex stimulation and procedures at the base of the skull with triplanar and three-dimensional reconstruction of the bony landmarks. A general use of the device for aiming at subcortical targets cannot be recommended. Limitations are the accuracy (≤ 2.2 mm) and software deficiencies and the lack of a reliable fixation of the position sensing arm (wand).